Pseudomyxoma peritonei: unusual origin from teratoma associated mucinous cystadenoma of ovary - Pandey, Manju; Shrestha, Binuma; Acharya, Bijay Chandra; Upreti, Suraj (Nepalese Journal of Cancer, 2021)
Pseudomyxoma peritonei is an extremely rare clinical syndrome with incidence of approximately two per 10000 laparotomies. Approximately 44% of women with PMP have ovarian mucinous tumor. It is generally accepted that the ovarian involvement is secondary; PMP is nearly always gastrointestinal origin, usually from mucinous adenoma of the appendix1. Exception to this, we report a 35 years lady who presented with the complaint of abdominal pain and abdominal distention for two months, clinically and radiologically gross mucinous ascites with large abdominopelvic mass was evident. Final histopathology was reported as mucinous cystadenoma, with mature teratoma components, appendix was normal.